Can attractant combined yellow sticky traps be used integrated pest management of invasive chestnut gall wasp [Dryocosmus kuriphilus Yasumatsu (Hymenoptera: Cynipidae)]? - Sarikaya, Oguzhan; Gencal, Tutku; Kadiogullari, Ali Ihsan; Yildiz, Yafes; Sarikaya, Ayse Gul; Gencal, Burhan; Sen, Ismail (Springer Int Publ Ag, 2025)
The chestnut gall wasp, Dryocosmus kuriphilus Yasumatsu (Hymenoptera: Cynipidae), was detected for the first time in Turkiye in 2014. The effectiveness in trapping the chestnut gall wasp by using sticky attractant traps combined with attractants during its active flying period was determined. The combination of yellow sticky traps with a mixture of 90% beer and 10% granulated sugar can have a significant impact on the populations of the pest. This method offers a high success rate in chestnut production regions due to reasons such as their success in attracting chestnut gall wasp adults, the fact that they do not have any negative effects on biological control studies carried out using Torymus sinensis, and offers an effective solution for chestnut gall wasp control without negative effects on nature and the environment.
Keywords: Attractant; Dryocosmus kuriphilus; Mass trapping; Sticky traps